A pegada de sexta-feira: notas para uma arquitectura partilhada - Tiago Lopes Tomé Farinha da Silva (2018)
This dissertation addresses the cultural role of architecture. Using the work of Daniel Defoe - TheLife and Strange Surprising Adventures of Robinson Crusoe - as a motto, we study the architect in threedifferent ways: fi rst, as a subjectivation of a cultural condition, capable of a unique view of objectsand reality; second, as an expressive agent of an idea of architecture, culture, art, language; and third, as aprecursor of a communicative relationship fulfi lled through architectural objects.We start by defi ning the act of knowledge based on the dialectic relation between subject and object,producer of a representative reality, linked to a personal and cultural image repertoire and conditionedby the circumstance in which the subject apprehends the surrounding environment. We also analyzethe process in which the images appear, born from the selection of sensitive data and the comparisonwith images held by memory. First, we explore the processes of signifi cation and culture, understandinghow the representations and images made by each subject base the identity and culture of a humansociety. We also see how language, which allows subjects to communicate the images on their repertoire,functions as an essential device for sharing this cultural identity, even if it is done by a repeatingupdate. Next, we understand how the communicative process, defi ned as an interaction betweenan emitter and a recipient via a signal, is dependent on the interpretation of a specifi c code and recipient.In a second phase, we study art from a cultural point of view, as a mean of transforming languageand convention. We se how a work of art is equally dependent on a subjective representation thatbestows it meaning. At the same time, we characterize the functional object linking it to a specifi c setof cultural, social, and historical expectations. Finally, we address the architectural object assigning itdenotative and connotative values that exist in relation with the subject's ability to recognize them.In the third phase of this dissertation, we deepen our knowledge of the dialectic relationship betweensubject and object, now from a corporal point of view. Starting with the concept of guest, whichsignifi es the meaning that eludes its host's intellect and hospitality, we address a pre-objective reality, bornout of the relation between the body and the things that surround it, that precedes the representation,signifi cation and cogitation of the subject. At last we arrive at the concept of habit, defi ned as temporaryresult of the mutual construction of man and world, which results of dwelling, defi ned as a humanway of being that maintains this construction ongoing.In the last part of the dissertation we compare what we have studied so far, so that we can expressthe main problem of this investigation. Using the concept of home, we encounter a poetic imaginationthat revolutionizes language, communication and geometry, and manifests the inhabitant's legitimatesearch for a place of reverie and dream. Not a place tied to the will and project of its architect, but aplace that evolves with the changing needs of its inhabitants, whether they're functional, symbolic,cultural, social or poetic.